Effect of half time cooling on thermoregulatory responses and soccer-specific performance tests - Zhang, Y.; Nepocatych, S.; Katica, C. P.; Collins, A. B.; Casaru, C.; Balilionis, G.; Sjökvist, J.; Bishop, P. A. (Montenegrin Journal of Sports Science and Medicine, 2014)
This study examined two active coolings (forearm and hand cooling, and neck cooling) during a simulated half-time recovery on thermoregulatory responses and subsequent soccer-specific exercise performance. Following a 45-min treadmill run in the heat, participants (N=7) undertook 15-min recovery with either passive cooling, forearm and hand cooling, or neck cooling in a simulated cooled locker room environment. After the recovery, participants performed a 6×15-m sprint test and Yo-Yo Intermittent Recovery Level 1 test (YYIR1) in a temperate environment. During the 15-min recovery, rectal temperature fell significantly (p<0.05) the sweat rate compared to passive cooling: 1.2±0.3 l/h vs. 0.8±0.1 l/h vs. 0.8±0.3 l/h, for passive cooling, forearm and hand cooling, and neck cooling, respectively. For passive cooling, elevated sweat rate resulted in higher (p<0.05) dehydration (2.1±0.3%) compared to neck cooling (1.5±0.3%) and forearm and hand cooling (1.4±0.3%). YYIR1 was improved (p<0.05) following forearm and hand cooling (869±320 m) and neck cooling (814±328 m) compared to passive cooling (654±311 m). Neck cooling (4.6±0.6) reduced (p=0.03) the session TS compared to passive cooling (5.3±0.5). These results suggest that active coolings effectively improved comfort and sweating response, which delayed exercise-heat induced performance diminish during a second bout of exercise.